Ever Thought About Strikes? Development of a Scale to Assess Attitudes and Behavioral Reactions to Strikes - Denise Vesper; Cornelius J. König (Journal of Business and Psychology, 2022)
AbstractStrikes are a recurrent phenomenon in many countries. However, research on strikes from a psychological perspective has been limited. By developing a sound measure to assess attitudes and behavioral reactions to strikes, we will be in a better position to evaluate these constructs in individuals and compare across studies. Therefore, we developed a scale to assess attitudes and behavioral reactions to strikes following classic scale development guidelines using four samples (total N0.167em=0.167em1369; N10.167em=0.167em304, N20.167em=0.167em209, N30.167em=0.167em443, N40.167em=0.167em413). In Study 1, we used exploratory factor analysis to reduce the generated items to a scale and showed that the strike attitude and behavioral reactions scale consists of one affective factor (negative reactions towards strikes), one cognitive factor (legitimacy of strikes), and three behavioral factors (informing oneself about strikes, strike-related social network behavior, and support of strikers). Study 2 confirmed these five factors and showed acceptable psychometric properties. Study 3 supported the construct validity of the developed scale: the five factors were correlated with willingness to strike and attitudes towards unions, among other variables. Study 4 further showed that the scale can also capture attitudes and behavioral reactions towards specific strikes. Overall, these studies indicate that the strike attitude and behavioral reactions scale is a psychometrically sound measure consisting of five factors.
Keywords: 650; Strikes; Attitudes; Scale development; Industrial relations; Unions